Prevalence of Internet addiction and its association with depression, anxiety and stress among medical students in Malaysia - Al-Ani, Ali Sabri Radeef; Faisal, Ghasak Ghazi (University of Messina, Italy, 2018)
Background: Using the internet excessively by students is known to cause internet addiction (IA) which may result in negative consequences such as decline in academic performance, social isolation, and emotional disturbances. This study aims to assess IA and its association with emotional disturbances among medical students. Methods: A sample of 268 medical students participated in this study. Internet addiction was assessed using Malay version of Chen Internet addiction Scale while the prevalence and severity of depression, anxiety and stress were assessed by Depression Anxiety, Stress Scale (DASS-21). 2 RADEEF & FAISAL Results: The rate of IA among students was 22.8%. No significant differences in terms of gender and other socio-demographic factors. IA was significantly associated and positively correlated with depression and anxiety symptoms but has inverse correlation with social interaction. Multiple linear regression analysis showed that stress (β = 0.261, P = 0.005) was a significantly important risk factor. Conclusions: IA is potentially high among medical students. Male and female students are equally affected. IA is significantly higher among students with poor social interaction. IA has a positive correlation with depression, anxiety and stress symptoms but inverse correlation with social interaction and stress can be considered as a predictive factor for IA.